Effects of riverine suspended particulate matter on the post-dredging increase in internal phosphorus loading across the sediment-water interface. (April 2016) - Liu, Cheng; Shao, Shiguang; Shen, Qiushi; Fan, Chengxin; Zhang, Lei; Zhou, Qilin
Abstract: Dredging is frequently used in the river mouths of eutrophic lakes to reduce internal phosphorus (P) loading from the sediment. However, the accumulation of P-adsorbed suspended particulate matter (SPM) from the inflowing rivers negatively affects the post-dredging sediment-water interface and ultimately increases internal P loading. Here, a 360-d experiment was carried out to investigate the influence of riverine SPM on the efficacy of dredging in reducing internal P loading. SPM was added to dredged and undredged sediments collected from the confluence area of Lake Chaohu. Several parameters related to internal P loading, including oxygen profile, soluble reactive P, and ferrous iron across the sediment-water interface, organic matter, alkaline phosphatase activity, and P fractions, were measured throughout the experimental period. The results showed that the P content (especially mobile P) in the sediment increased to the pre-dredging level with the accumulation of SPM in the dredged sediment. In addition, the P flux across the sediment-water interface increased with the accumulation of SPM. Several characteristics of SPM, including high organic matter content, mobile P, high activity of alkaline phosphatase, and high biological activity, were considered correlated with the post-dredging increase in internal P loading. Overall, this study showed that the heavily contaminated riverine SPM regulates the long-term efficacy of dredging as a nutrient management option in the confluence area. Management is needed to avoid or reduce this phenomenon during dredging projects of this nature. Highlights: The post-dredging increase in internal P loadings was studied. Riverine suspended particulate matter led to the increase in internal P loadings. Organic matter, Fe–P, and biological activity correlated with internal P increase. Particulate matter regulates reduction effects of internal P in confluence areas. Abstract : The efficacy of dredging in reducing internal phosphorus loading in the confluence area is highly regulated by the contaminated riverine suspended particulate matter.